PENGARUH METODE BERNYANYI TERHADAP HASIL BELAJAR IPS MATERI PAKAIAN ADAT PADA SISWA KELAS IV SDN 17 TANJUNG BATU - Furi Ayu Novia Utami; Yasir Arafat; Eni Heldayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Problem of this research is that the completeness of student social studies learning outcomes is still relatively low, students are less enthusiastic and quickly bored during the learning process and the methods used is the conventional method. The purpose of the study was to determine the influence of singing methods on social studies learning outcomes of traditional clothing materials in grade IV students of SDN 17 Tanjung Batu. The research method uses the Quasi- Experimental Design experimental method with Nonequivalent Control Group Design design. Data collection techniques include observation, tests and documentation. Data analysis techniques use normality tests, homogeneity tests and hypothesis tests using t-tests. Based on the results of research that has been conducted by researchers, the results of the average pretest and posttest scores, the pretest score in the experimental class is 68.09 and the posttest score amounted to 80. In addition, we can also see from the hypothesis testing of the t-test that has been carried out with the acquisition of > values, namely with a value of 2,500 > 2,021, so that Ho is rejected and Ha is accepted. This means that there is an influence of singing methods on social studies learning outcomes of traditional clothing materials in grade IV students of SDN 17 Tanjung Batu. Keywords: Singing Method, Learning Outcomes